The Effect of Understanding Tax Regulations on Taxpayer Compliance with the Business Development Service Program as a Moderation Variable - Anisa, Nur; Fakhroni, Zaki (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to determine the relationship between understanding tax regulations and taxpayer compliance moderated by the business development service program at KPP Pratama Samarinda Ilir. The population in this study were Individual Taxpayers of Micro, Small and Medium Enterprises (MSMEs) registered at KPP Pratama Samarinda Ilir, using the purposive sampling method, there were 78 respondents. The data collection method used a questionnaire. Data analysis used SmartPLS Version 4.1.0.6. Based on the results of the study, empirical evidence was obtained that (1) understanding tax regulations has a positive and significant effect on taxpayer compliance. (2) The business development service program has a positive but insignificant effect in moderating the relationship between understanding tax regulations and taxpayer compliance